Transmission chain error elimination for gear hobbing machines based on classified compensation theory and frequency response identification. (May 2020) - Xia, Changjiu; Wang, Shilong; Long, Tan; Ma, Chi; Wang, Sibao
Highlights: A new compensation method is proposed to eliminate TCE of gear hobbing machines. TCE is decomposed into three types of error components for compensation. Feasibility and effectiveness is verified on a YS3120-type gear hobbing machine. TCE can be reduced by more than 80%, laying the foundation for precision hobbing. Abstract: This paper proposes a novel classified compensation method considering frequency response to eliminate the transmission chain error (TCE) of gear hobbing machines. Based on error source analysis and Discrete Fourier Transform (DFT), the measured TCE was firstly decomposed into different error components, including the integer harmonic, the non-integer harmonic and the other. A classified compensation theory was then presented, in which the Measurement System Error Compensation (MSEC) and the software axis were used to compensate the first two types of error components, respectively. Then, the frequency response identification for the C-axis control system was performed, and the final compensation values were calculated and integrated into the classified compensation process. The experimental results on a YS3120-type gear hobbing machine showed that the peak-to-peak value of TCE was reduced by 85.5% and that both the integer and non-integer harmonic errors were effectively compensated. It lays the foundation for gear precision hobbing.